Home-Based Up-Dosing in Build-Up Phase of Oral Immunotherapy of Egg Allergy Is Safe and Feasible in Real-World Practice - Jeong, Hye-In; Lee, Bora; Kim, Sukyung; Kyung, Yechan; Jung, Minyoung; Kim, Minji; Lee, Ji Young; Kim, Kevin; Ahn, Kangmo; Kim, Jihyun (Allergy, asthma & immunology research, 2021)
Oral immunotherapy (OIT) has emerged to build sustained unresponsiveness or tolerance in patients with egg allergy. However, it is important to increase compliance and ensure safety because OIT requires an extended period of time and has a risk of side effects like anaphylaxis. We aimed to show the feasibility and safety of OIT during the build-up phase using a home-based, up-dosing method in children with egg allergy. Sixteen patients aged 4 to 12 years with egg allergy were enrolled. Patients increased the dose of boiled egg white (EW) by 5% per day at home and 25% per month at the hospital, with a target dose of 40 g of boiled EW (4.0 g of EW proteins). A historical control group (n = 16) was matched for age, sex, and clinical characteristics for comparisons with the OIT group. Oral food challenge (OFC) tests were performed after completing the build-up phase. In the OIT group, 93.8% (15/16) of patients achieved desensitization, with only 1 patient discontinuing OIT before the maintenance phase due to repeated allergic reactions. Mild allergic reactions and anaphylaxis occurred in 12 (75.0%) and 2 patients (12.5%), respectively. However, there were no significant adverse reactions such as serious anxiety or life-threatening events that required discontinuation of treatment. On the contrary, only 1 patient (6.3%) in the control group passed an OFC of 40 g of boiled EW during the same period (P < 0.001). Our results suggest that home-based up-dosing protocols using boiled eggs may be safe and feasible for the build-up phase of OIT in children with egg allergy.